Deformation mechanisms of thermoplastic elastomers: Stress-strain behavior and constitutive modeling. (16th October 2017) - Cho, Hansohl; Mayer, Steffen; Pöselt, Elmar; Susoff, Markus; in 't Veld, Pieter J.; Rutledge, Gregory C.; Boyce, Mary C.
Abstract: This work addresses the large strain behaviors of thermoplastic polyurethanes (TPUs) spanning a range of fractions of hard and soft contents in both experiment and theoretical modeling. The key mechanical features involve a combination of elasticity and inelasticity, and are quantified experimentally under a broad variety of loading scenarios. A finite deformation constitutive model is then presented to capture the main features of the stress-strain data, which are strongly dependent on fractions of hard and soft contents. The stress-strain behavior of these TPUs is characterized by highly nonlinear rate-dependent hyperelastic-viscoplasticity, in which substantial energy dissipation is accompanied by shape recovery as well as softening. Agreement between the model and the experimental data for the representative TPUs provides physical insight into the underlying deformation mechanisms in this important class of soft materials that exhibit both elastomeric and plastomeric characteristics. Graphical abstract: Large strain behavior of thermoplastic polyurethanes spanning a range of fractions of hard and soft segment contents: shape recovery and energy dissipation upon cyclic loading conditions are highly dependent on the fractions of hard and soft contents, spanning the range from glassy to rubbery polymers. Highlights: Large strain behavior of thermoplastic polyurethanes is examined under various loading scenarios Mechanical behavior characterized by nonlinear rate-dependent hyperelastic-viscoplasticity Finite deformation constitutive model is presented that captures mechanical response Interpretation of constitute model provides insight into deformation mechanisms